THE USE OF TARSE ART IN THE POETRY OF SHOIRA SHAMS - Bobonazarova Gulzoda (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article deals with the use of verbal arts, mainly tarse art, in the lyric works of Shoira Shams. we paid attention and tried to explain the meaning by means of examples